Characteristics of methanotrophic communities and their physicochemical driving mechanisms in estuarine and nearshore wetlands of Qinghai Lake - Wei Ji; Likai Ren; Zhiyun Zhou; Jianpeng Yang; Ziwei Yang; Ni Zhang; Jianqing Sun; Kelong Chen; Wenbo Chai (iScience, 2025)
Summary: Methanotrophic communities play a vital role in regulating methane fluxes in wetland ecosystems. This study examined the composition and environmental drivers of methanotrophs in estuarine and nearshore wetlands of the Qinghai Lake basin. Soil samples from six sites across three tributaries showed clear spatial and vertical variation in organic matter, nitrogen forms, and salinity. The Heima River estuarine wetland exhibited the highest methanotrophic diversity and functional potential. Dominant genera included Methylobacter, Methylosinus, and Methylocystis, with site-specific distributions. Redundancy analysis identified soil organic matter, nitrate nitrogen, pH, and electrical conductivity as key factors shaping community structure. These findings reveal how water-salt interactions and nutrient status influence methane-oxidizing microbes, offering insights into carbon cycling dynamics in high-altitude wetlands and supporting ecological restoration efforts in plateau regions.